2010
DOI: 10.1158/0008-5472.can-09-4336
|View full text |Cite
|
Sign up to set email alerts
|

Role of H2O2 in RET/PTC1 Chromosomal Rearrangement Produced by Ionizing Radiation in Human Thyroid Cells

Abstract: During childhood, the thyroid gland is one of the most sensitive organs to the carcinogenetic effects of ionizing radiation that may lead to papillary thyroid carcinoma (PTC) associated with RET/PTC oncogene rearrangement. Exposure to ionizing radiation induces a transient "oxidative burst" through radiolysis of water, which can cause DNA damage and mediates part of the radiation effects. H 2 O 2 is a potent DNAdamaging agent that induces DNA double-strand breaks, and consequently, chromosomal aberrations. Irr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(44 citation statements)
references
References 41 publications
1
36
0
5
Order By: Relevance
“…Exogenous H 2 O 2 induces DNA damage in thyroid cells (6,20). To establish a link between H 2 O 2 -generating NADPH oxidase DUOX1 activation and DNA damage observed several days after irradiation, we performed RNA interference experiments ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Exogenous H 2 O 2 induces DNA damage in thyroid cells (6,20). To establish a link between H 2 O 2 -generating NADPH oxidase DUOX1 activation and DNA damage observed several days after irradiation, we performed RNA interference experiments ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Hypoxia and antioxidant therapy reduce the X-ray-induced delayed effects, suggesting that radio-induced oxidative stress plays a significant role in determining the susceptibility of irradiated cells to genetic instability (3)(4)(5). We recently showed that H 2 O 2 is able to cause RET/PTC1 rearrangement in thyroid cells, indicating that oxidative stress could be responsible for the RET/PTC rearrangement frequently found in radiation-induced thyroid tumors (6).…”
mentioning
confidence: 99%
“…Because of its numerous advantageous properties, HyPer holds promise for understanding the biological roles of H 2 O 2 , and its signal has been characterized to an extent and used in many different contexts [15][16][17][18][19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…This finding could be explained by the significant decrease in RET/PTC over the years and the equivalent increasing rate of BRAFV600E and RAS mutations in PTC, possibly attributed to the decreased exposure to ionizing radiation in the last decades or to new pollutants (75,76,77,78,79).…”
Section: Discussionmentioning
confidence: 99%